Identification of Irrigation Performance Indicator using Remote Sensing - Roy, Andreas F.V.; Zicco, Zicco; Setiawan, Theresita Herni; Djaja, Jonathan; Eddy, Liyanto; Adianto, Yohanes L.D. (Rekayasa Sipil, 2023)
Irrigation system is one of the important physical infrastructures for achieving the objectives of the Sustainable Development Goals program in 2030. Good performance of the irrigation system will positively contribute to the agricultural sector and improve the farmer welfare. Indonesia has a modern irrigation management unit which is responsible for the operation and maintenance of irrigation in an irrigation area with participatory, needs-based, effective, efficient and sustainable principles that guarantee a better level of service for water-using farmers. Remote sensing technology has the potential to assist in the new assessment process on existing irrigation systems to improve agricultural quality. Therefore this paper aimed to identify irrigation performance indicators that can be measured using remote sensing to help the development and the operation & maintenance of modern irrigation systems in Indonesia become more effective, efficient, and sustainable. The method used the Simplified Surface Energy Balance (SSEBop) model to calculate the actual evapo-transpiration value. The study case was on Balai Besar Wilayah Sungai Cimanuk-Cisanggarung West Java irrigation area produces actual evapo-transpiration values that were described spatially of 1.59 to 5.99 mm per day. Low levels of actual evapo-transpiration indicated that plants lack of water or deficit irrigation. Therefore, the actual evapo-transpiration values can be used to improve service level performance on modern irrigation systems in Indonesia such as water loss, water supply, irrigation water allocation, and water allocation interval.